AUGMENTED REALITY MAPS AS AN ALTERNATIVE HISTORY LEARNING MEDIA FOR VOCATIONAL STUDENTS - Hawiki Renalia; Blasius Suprapta (Universitas Negeri Malang, 2022)
This research focuses on the significance of responding to massive changes in historical learning. However, various learning issues arise, resulting in a lack of understanding of the content by students, particularly those who have not previously understood Indonesian History material well. This is due to dense learning materials and the use of ineffective learning media. As a result, students struggle to understand the material in the text-book. Based on this, learning innovations that facilitate learning Indonesian history are required. One of them is the study of prehistoric people's lives, which includes historical values, using augmented reality visual media. This media has the ability to clarify ideas, increase students' imagination and interest, and thus increase understanding of the material. Augmented reality packaged digitally can directly create interaction between students and 3D objects, facilitating information delivery. The goal of this study is to create learning media ARMAPS (Augmented Reality Maps) and evaluate their effectiveness. A 4D model was used in this study, which included: (1) definition, (2) design, (3) development, and (4) dissemination.